Contribution to the knowledge of the oribatid mite family Nesozetidae (Acari, Oribatida) - Ermilov, Sergey G.; Hugo-Coetzee, Elizabeth A.; Theron, Pieter D.; Behan-Pelletier, Valerie M. (Zootaxa, 2017)
A new oribatid mite species of the genus Nesozetes (Oribatida, Nesozetidae) is described from moss (Sphagnum sp.) on the seepage area below a permanent spring in South Africa. Nesozetes membranus sp. nov. differs from its only congener, Nesozetes rostropterus, described from Fiji, by the presence of a second pair of membranes located in the podosomal region, setiform bothridial setae and striate subcapitular mentum. A revised diagnosis of Nesozetidae, discussion on its taxonomic status, and information on distribution and ecology of Nesozetes species are given.